Vietnamese Evangelicals and Pentecostalism : the politics of divine intervention - Le, Vince (Global Pentecostal and Charismatic Studies, 2018)
This book offers an analysis of the historical, theological, and social conditions that give rise to the growth of pentecostalism among contemporary Vietnamese evangelicals. Emerging from the analysis is an understanding of how underprivileged evangelicals have utilized the pentecostal emphasis on divine intervention in their pursuit of the betterment of life amid religious and ethnic marginalization. Within the context of the global growth of pentecostalism, Vietnamese Evangelicals and Pentecostalism shows how people at the grassroots marry the deeply local-based meaning dictated by the particularity of living context and the profoundly universal truth claims made by a religion aspiring to reach all four corners of the earth to enhance life.